Distribution of plasminogen activator inhibitor (PAI-1) in tissues. Issue 2 (February 1991) - Simpson, A J; Booth, N A; Moore, N R; Bennett, B
Abstract : Extracts of human tissue were analysed for plasminogen activator inhibitor (PAI-1) antigen and activity. PAI-1 was localised in tissues by an immunochemical method, using monoclonal antibodies. PAI-1 occurred throughout the body; its concentration and activity differed considerably from organ to organ. Extracts of liver and spleen had the greatest abundance of PAI-1, but the activity of the inhibitor was much higher in liver than in spleen: the liver may be a source of plasma PAI-1. Immunochemical staining for PAI-1 was observed in endothelium, platelets and their precursor cells, the megakaryocytes, and locations central to the process of haemostasis. PAI-1 also occurred in neutrophil polymorphs and macrophages, cells important in inflammatory and immune processes, but not in lymphocytes. Other cell types, in particular, vascular smooth muscle cells and mesangial cells, also stained positively for PAI-1 and such cells seem to represent an important reservoir of PAI-1.